2010
DOI: 10.1002/asmb.812
|View full text |Cite
|
Sign up to set email alerts
|

Implementing loss distribution approach for operational risk

Abstract: To quantify the operational risk capital charge under the current regulatory framework for banking supervision, referred to as Basel II, many banks adopt the Loss Distribution Approach. There are many modeling issues that should be resolved to use the approach in practice. In this paper we review the quantitative methods suggested in literature for implementation of the approach. In particular, the use of the Bayesian inference method that allows to take expert judgement and parameter uncertainty into account,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 54 publications
(104 reference statements)
0
26
0
1
Order By: Relevance
“…So far, the operational risk literature could not present clear evidence favoring one approach over the other. For instance, using a simulation study, Shevchenko (2010) shows that for light-tail lognormal severity distributions, the shifting approach might induce significant bias in comparison to the truncation approach, but this bias becomes insignificant for heavy-tail lognormal distributions. Meanwhile, simulation studies performed by Cavallo et al (2012) under the shifting approach reveal that the overstatement or understatement of the severity of an individual loss in the extreme right tail depends on the characteristics of the data sample.…”
Section: Introductionmentioning
confidence: 99%
“…So far, the operational risk literature could not present clear evidence favoring one approach over the other. For instance, using a simulation study, Shevchenko (2010) shows that for light-tail lognormal severity distributions, the shifting approach might induce significant bias in comparison to the truncation approach, but this bias becomes insignificant for heavy-tail lognormal distributions. Meanwhile, simulation studies performed by Cavallo et al (2012) under the shifting approach reveal that the overstatement or understatement of the severity of an individual loss in the extreme right tail depends on the characteristics of the data sample.…”
Section: Introductionmentioning
confidence: 99%
“…There are several modeling issues that should be resolved to use this approach in practice, a detailed review on the quantitative properties of estimation can be found in [19], [20], [21], [22], [23], [23], [24] and in addition in some important heavy tailed settings (large consequence, rare occurance) closed form representations of such models in [25], [16] and [15].…”
Section: A Brief Background On Loss Distributional Approach (Lda) Modelsmentioning
confidence: 99%
“…A severity distribution function F is said to have a dominantly varying tail if it satisfies the asymptotic condition that 20) for any u ∈ (0, 1). An alternative equivalent relationship is to consider…”
Section: Remark 217 (Implications For Capital Approximations)mentioning
confidence: 99%
“…If details of the insurance policies are known (e.g. top cover limit, excess amount, etc), see Shevchenko (2009), then it should not be difficult to account for insurance recoveries, when the annual loss distribution over next reporting year is estimated via simulation of the frequencies and severities. Often, event times are needed to calculate the insurance recoveries and these are easily simulated for Poisson processes considered in this paper.…”
Section: Modelmentioning
confidence: 99%
“…There are various important aspects of operational risk modeling discussed in the literature, e.g. Chavez-Demoulin et al (2006), Cruz (2002Cruz ( , 2004 and Shevchenko (2009) to mention a few. One of the challenges in modelling operational risk is the lack of complete data -often a bank's internal data are not reported below a certain level (typically of the order of €10,000).…”
Section: Introductionmentioning
confidence: 99%